"I can join a sport class, but school has to come first": adolescent athletes` dual career construction styles in lower secondary sport schools - Kuokkanen, J.; Saarinen, M.; Romar, J. E.; De Brandt, K. (International Journal of Sport and Exercise Psychology, 2025)
In this longitudinal qualitative study, we explored the automatic and controlled processes underpinning adolescent athletes` dual career (DC) construction styles in lower secondary school and how these styles influenced the continuation of sports in upper secondary education. We conducted semi-structured interviews with 16 Finnish adolescent lower secondary school DC athletes (nine females, seven males) aged 14.5 years at baseline, interviewed them one year later, and then analyzed the data using reflexive thematic analysis based on dual-process theory. Most adolescent athletes (11 of 16) constructed their DCs in Grade 8 (T1) using a contrapuntal DC construction style, attempting to balance sports and academic studies. Eleven adolescent athletes maintained their DC styles, but five shifted their career styles between T1 and T2. Exemplifying the dynamic and individual construction of their DCs, seven adolescents had a contrapuntal style, three a dissonant style, and six a monophonic style in Grade 9 (T2). Four of sixteen continued their DCs in sports-oriented upper secondary education, all of them exhibiting a contrapuntal style. The remaining 12, representing all 3 styles, transitioned to general upper secondary schools. Dual-process theory facilitated the identification of specific automatic and controlled processes that influenced decision-making among adolescents with different career construction styles. This understanding can aid in tailoring individual DC services to effectively support adolescents in balancing their school and sports pursuits during lower secondary school and assist them in transitioning to their preferred study options in upper secondary school.